2009
DOI: 10.4014/jmb.0901.0059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Three Culture Methods for the Isolation of Mycobacteria from Clinical Samples

Abstract: We assessed the capacity of two liquid-medium culture methods with automated incubation and reading systems (MB/BacT ALERT 3D System and BACTEC MGIT 960 System) and one solid-medium culture method (Löwenstein-Jensen) to detect mycobacteria in different types of clinical samples. Out of 1,770 cultured clinical samples (1,519 of respiratory origin and 251 of nonrespiratory origin), mycobacteria were isolated in 156 samples (135 M. tuberculosis complex, 8 M. chelonae, 6 M. kansasii, 4 M. fortuitum, 2 M. gordonae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
5
19
1
4
Order By: Relevance
“…Additional studies incorporating patient characteristics with TTD data would be of value in elucidating TTD disparities. Our findings of the ability of the MGIT system to more rapidly detect mycobacteria than the BacT/Alert system correspond to those in other studies that compared the two (19,27,31,34). Other investigators have suggested that the addition of vancomycin to the BacT/Alert antibiotic supplement (19) or differences in the detection mechanisms (34) may be partially responsible.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additional studies incorporating patient characteristics with TTD data would be of value in elucidating TTD disparities. Our findings of the ability of the MGIT system to more rapidly detect mycobacteria than the BacT/Alert system correspond to those in other studies that compared the two (19,27,31,34). Other investigators have suggested that the addition of vancomycin to the BacT/Alert antibiotic supplement (19) or differences in the detection mechanisms (34) may be partially responsible.…”
Section: Discussionsupporting
confidence: 78%
“…Other investigators have suggested that the addition of vancomycin to the BacT/Alert antibiotic supplement (19) or differences in the detection mechanisms (34) may be partially responsible. Additional findings from our study revealed the high sensitivities of the two broth systems for detection of MTBC, which were comparable to those reported by others evaluating these systems (1,12,23,24,27,34). However, none of those studies differentiated initial diagnostic from follow-up specimens.…”
Section: Discussionsupporting
confidence: 77%
“…In similar studies, all specimens submitted to a particular microbiology laboratory were combined; thus, the percentage of positive smears and cultures detected was lower (8-50%) [2][3][4]8]. The inclusion of clinical specimens from suspected cases of pulmonary TB, together with clinically and radiologically identified pulmonary tuberculosis, increased the number of positive cases in our study compared to others.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, routine laboratory use of the MGIT system has been suggested. Furthermore, the use of both the MGIT 960 culture system and the classical culture methods yields higher reproduction rates [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Kultura mokraće je senzitivna u 80% do 90% slučajeva i ima specifičnost od skoro 100% (13). I pored toga, potrebno je duže vreme do dobijanja rezultata (i do 6 ne-delja), a razlog je spor rast mikobakterija na podlozi (5).…”
Section: Dijagnozaunclassified